2012
DOI: 10.1186/1471-244x-12-27
|View full text |Cite
|
Sign up to set email alerts
|

Choice of antipsychotic treatment by European psychiatry trainees: are decisions based on evidence?

Abstract: BackgroundLittle is known about the factors influencing treatment choice in psychosis, the majority of this work being conducted with specialists (consultant) in psychiatry. We sought to examine trainees' choices of treatment for psychosis if they had to prescribe it for themselves, their patients, and factors influencing decision-making.MethodsCross-sectional, semi-structured questionnaire-based study.ResultsOf the 726 respondents (response rate = 66%), the majority chose second-generation antipsychotics (SGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…These results are consistent with those of a study conducted in the USA by Huskamp 10. Moreover, previous studies have shown that psychiatry trainees would largely choose olanzapine, risperidone or aripiprazole as treatments for themselves and consider efficacy and tolerability to be the most important factors in this choice 16. From these results we might conclude that physicians are honestly convinced about the superior efficacy and tolerability of SGA over FGA.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with those of a study conducted in the USA by Huskamp 10. Moreover, previous studies have shown that psychiatry trainees would largely choose olanzapine, risperidone or aripiprazole as treatments for themselves and consider efficacy and tolerability to be the most important factors in this choice 16. From these results we might conclude that physicians are honestly convinced about the superior efficacy and tolerability of SGA over FGA.…”
Section: Discussionsupporting
confidence: 90%
“…The outcomes mirror a larger study of European psychiatry trainees which found that 93% of respondents would pick an atypical antipsychotic (SGA) for themselves. 4 This finding was not due to ignorance of the published research, as trainees who were aware of the major studies questioning the efficacy of SGAs were even more likely to prescribe SGAs. This finding is also unlikely to be explained by length of time spent working in psychiatry as the researchers found that attitudes did not differ by length of training.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals also report overwhelming preference for SGAs as a treatment of choice if needed for themselves. 4 However, the rationale for this trend is not clear, especially in the face of research evidence. 5 , 6 CATIE and CUtLASS 1, two large, non-commercial clinical trials comparing FGAs and SGAs for people with chronic schizophrenia in the USA and the UK respectively, have shown that the SGAs in general are no more effective (except clozapine) or better tolerated than the older drugs.…”
mentioning
confidence: 99%
“…Our findings indicate that of all considered oral antipsychotic drugs, only risperidone was found to be asso- ciated with self-stigmatisation: its use was linked to lower severity of Alienation and a greater degree of Stigma resistance. Risperidone is a member of the second-generation group of antipsychotic drugs, which is currently recognised as first choice in schizophrenia treatment due to its relative safety and efficacy [30]. Although no previous data exists on the link between the use of risperidone and internalised stigma, data from one randomised controlled trial suggests that risperidone may improve social engagement, cooperative behaviour and the interpersonal trust of patients with schizophrenia, which may prevent the patient experiencing a sense of alienation [31].…”
Section: Antipsychotic Treatment As a Predictor Of Self-stigmamentioning
confidence: 99%